A Comprehensive Study on the Effect of Roasting and Frying on Fatty Acids Profiles and Antioxidant Capacity of Almonds, Pine, Cashew, and Pistachio - Hadeel Ali Ghazzawi; Khalid Al-Ismail (Journal of Food Quality)
The aim is to evaluate the effects of frying and roasting on nuts. Frying and roasting were performed according to the local Jordanian home-made cuisine, and the nuts under experiment were raw almonds, pine, cashew, and pistachio. Nuts samples were roasted at 110°C for 16 minutes and fried at 175°C for 2.5 minutes. The results show that both roasting and frying of nuts did not affect the flavonoids content except for roasted pistachios where significant rise of flavonoids content was detected. Total phenolic content showed no significant differences except for pine nuts in which it increased significantly in both roasting and frying. Oxidative stability, presented by 1,1-diphenyl-2-picryl-hydrazyl (DPPH), was significantly different in all nuts except for pistachio nuts that have shown no differences. Fatty acids profile, presented by saturated fatty acids (SFA), oleic acid (OL), and essential fatty acids (EFA), was affected significantly by roasting and frying, especially for SFA in almonds and pine nuts and α-linoleic acid (ALA) contents of pine. In conclusion, the effects of roasting and frying on the aforementioned nuts species were positive for fatty acids profile and antioxidants activity.